Answer:
The answer in the procedure
Step-by-step explanation:
we have
2x-3y=-1 ----> equation A
3x+3y=26 --> equation B
Solve the system by elimination
Adds equation A and equation B
2x-3y=-1
3x+3y=26
----------------
2x+3x=-1+26
5x=25
x=25/5
x=5
Find the value of y
substitute the value of x in equation A or equation B and solve for y
2(5)-3y=-1
10-3y=-1
3y=10+1
y=11/3
Answer:
19/24m-1/3
Step-by-step explanation:
1/6m-(-5/8m+1/3)=1/6m+5/8m-1/3=4/24m+15/24m-1/3=19/24m-1/3
Answer:
in this question use the triangle property
A+B+C=180
than you will get the value of x
The correct answer is 60cm^2 because the area of a triangle is half base*height -> 30/2*40
No 1.2 x 2.6 doesn't equal 31.2 it equals 3.12